2002
DOI: 10.1111/j.1744-6570.2002.tb00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping With an Organizational Merger Over Four Stages

Abstract: This longitudinal study examined how individuals cope over 4 stages of a merger. The study replicated and extended past coping research by examining changes in coping variables over time. Employee appraisals, coping resources, negative emotions, and emotion‐focused and problem‐focused coping strategies were measured. Negative appraisal, social support, perceived control, and emotion‐focused coping significantly changed across stages. Coping variables exhibited linear, quadratic, and cubic trends over time, hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
147
2
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(165 citation statements)
references
References 63 publications
6
147
2
10
Order By: Relevance
“…In the anticipation stage of change, when perceptions of job uncertainty were high and perceptions of personal control were low, job uncertainty had both a direct and indirect effect on emotional exhaustion. The positive and direct association between job uncertainty and emotional exhaustion may be due to issues relating to future job changes being particularly salient as employees anticipate downsizing (Fugate et al, 2002;Schweiger & Denisi, 1991;Pollard, 2001). Although personal control partially mediated its effects, job uncertainty related to these issues continued to have a direct effect on the level of emotional exhaustion during this stage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the anticipation stage of change, when perceptions of job uncertainty were high and perceptions of personal control were low, job uncertainty had both a direct and indirect effect on emotional exhaustion. The positive and direct association between job uncertainty and emotional exhaustion may be due to issues relating to future job changes being particularly salient as employees anticipate downsizing (Fugate et al, 2002;Schweiger & Denisi, 1991;Pollard, 2001). Although personal control partially mediated its effects, job uncertainty related to these issues continued to have a direct effect on the level of emotional exhaustion during this stage.…”
Section: Discussionmentioning
confidence: 98%
“…Coupled with the often disempowering experience of downsizing (see Mishra & Spreitzer, 1998), these heightened levels of uncertainty can lead to perceptions of a lack of personal control over the future. For instance, Fugate and colleagues (Fugate, Kinicki & Scheck, 2002) found that levels of personal control were lowest during the anticipation stage of a merger, where levels of uncertainty were high because employees were expecting job losses. Personal control increased over time as employees learnt about how the change would affect them.…”
Section: Anticipating Downsizingmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the framework has been used to explain individual stress responses in settings which are similar, such as a job loss (Hamilton, Hoffman, Broman, & Rauma, 1993;Gowan, Riordan, & Gatewood, 1999), or mergers and acquisitions (Scheck & Kinicki, 2000;Fugate, Kinicki, & Scheck, 2002). Second, from the large number of occupational stress theories, Lazarus' framework of stress and coping (1984) is most suitable to answer our research question.…”
Section: Theoretical Background: Lazarus' Theory Of Stress and Copingmentioning
confidence: 99%
“…When employees experience the emotions of change they may find the support of others, including their managers, to be beneficial (Fugate et al, 2002). The literature on stress has shown that helpful responses from others, including leaders of change, assist people in coping with demanding experiences (Folkman and Lazarus, 1988;Robinson and Griffiths, 2005).…”
mentioning
confidence: 99%